Three-Method Hybrid Numerical Simulation for Surface-Plasmon-Enhanced GaInN-Based Light-Emitting Diodes with Metal-Embedded Nanostructures - Hiramatsu, Ryoya; Takahashi, Ryo; Fujiki, Ryoto; Hozo, Keisuke; Sawai, Kanato; Han, Dong-Pyo; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu (Frontiers in Physics, 2021)
In this paper, a hybrid numerical simulation tool is introduced and performed for GaInN-based light-emitting diodes (LEDs) with metal-embedded nanostructure to theoretically predict external quantum efficiency (EQE), which composed of finite-difference time-domain, rigorous coupled wave analysis, and ray tracing. The advantage is that the proposed method provides results supported by sufficient physical background within a reasonable calculation time. From the simulation results, the EQE of LED with Ag-nanoparticles embedded nanostructure is expected to be enhanced by as high as 1.6 times the conventional LED device in theory.